EFFECT OF A STRENGTH TRAINING PROTOCOL AND THE TESTOSTERONE PROPIONATE ADMINISTRATION IN BODY WEIGHT, HEART WEIGHT AND LEFT VENTRICLE WEIGHT OF WISTAR RATS. (Fiep Bulletin - online, 2011)
The objective of our study was to compare body weight, heart weight, left ventricle (LV), heart weight/body weight (HW/BW) and LV weight/heart weight (LVW/HW) coefficient of adult and old-aged rats submitted to an exercise protocol with testosterone-administration. Twenty seven male Wistar rats, divided into Group C (Control), 4 thirteen-month-old rats; Group S (Sedentary), 6 sixteen-month-old rats; Group ST (sedentary with testosterone), 6 sixteen-month-old rats; Group T (trained), 5 rats submitted to an exercise protocol from 13 to 16 months old; and Group TT (Trained with testosterone), 6 rats submitted to an exercise protocol from 13 to 16 months old. At 16 months old the animals were submitted to anesthesia, sacrified and had their hearts removed, seccioning the base vessels near the organ. All hearts were weighed in a digital analytical scale using Scherle method. Body and heart, left ventricle (LV) weights, HW/BW, LVW/HW were analyzed. For the statistical analysis ANOVA and Turkey post-test with significance levels of 5% were used. The body weight increased 2.5% in group S compared to group C. The other groups showed decrease of 7% compared to C. The heart weight increase in 15,2% in group S in relation to group C. Groups T, ST and TT have shown that the exercise associated with testosterone propionate produced weight and LV weight changes.
Keywords: left ventricle; anaerobic exercise; testosterone propionate